Severe Macular Edema in Patients with Juvenile Idiopathic Arthritis-Related Uveitis - Maria Pia Paroli; Claudia Fabiani; Giovanni Spinucci; Irene Abicca; Alfredo Sapia; Leopoldo Spadea (Case Reports in Ophthalmological Medicine)
Purpose. To report the onset of severe macular edema in adolescent female patients affected by juvenile idiopathic arthritis (JIA). Methods. Four female patients affected by JIA-related chronic anterior uveitis (CAU), complicated by severe macular edema, were retrospectively analyzed. Macular area was evaluated by fluorescein angiography and optical coherence tomography (OCT). Results. CAU was bilateral in three patients. Mean age of uveitis and arthritis onset was, respectively, 4.5±1.7 years and 6.0±3.9 years. All patients underwent cataract extraction surgery. Despite ocular inflammation being controlled by topical/systemic therapy, during adolescence (mean age of appearance/diagnosis: 12.7±3.9 years) patients developed severe unilateral macular edema. OCT revealed massive macular thickening (range from 550 μm to 1214 μm). Conclusions. Macular edema appeared in female adolescent patients in eyes with long-dating CAU submitted to cataract surgery. In such patients, in presence of age-related microvascular changes due to the enhancer effect of sex hormones, cataract extraction should be a factor triggering the retinal complication.